Analysis of abundance of microplastic in fish caught in Percut Waters - Tia Angraini; Fatimah Fatimah; Hesti Wahyuningsih (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2024)
Plastic waste that is not managed properly will damage the environment by polluting the ecosystem. Plastic in waters can turn into micro-sized plastic waste. Plastics whose size is less than 5 mm are called microplastics. The emergence of microplastic pollutants is caused by increasing population activity in Percut Waters. Percut waters are waters located in the coastal area of North Sumatra where there are many anthropogenic activities that cause the emergence of microplastics. Microplastics can have a negative impact on exposed marine biota. Nowadays microplastics are not only found in the environment, but can also accumulate in the bodies of organisms, for example. This research aims to determine the abundance of microplastics in fish found in Percut waters. The research was carried out in October November 2022 in Percut Waters. Fish samples were caught using nets and the samples were separated from their digestive tract and diluted with the addition of NaCl and H2O2 lauric. The average abundance of microplastics in fish samples ranged from 24294 particles. The fish species where the most microplastics were found was mullet fish with 294 particles. The most common types of microplastics found in total are fiber microplastics.Keywords:MicroplasticDigestionCoastalPercut